2012
DOI: 10.1017/s1047951112000303
|View full text |Cite
|
Sign up to set email alerts
|

Value of history taking in children and adolescents with cardiac syncope

Abstract: Children and adolescents with a history of abnormal electrocardiogram findings and exercise-related syncope spells were at high risk for cardiac syncope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 22 publications
(84 reference statements)
2
33
0
3
Order By: Relevance
“…624,628 Risk factors that raise suspicion of a cardiac etiology include the absence of prodromal symptoms, presence of preceding palpitations within seconds of loss of consciousness, lack of a prolonged upright posture, syncope during exercise or in response to auditory or emotional triggers, family history of SCD, abnormal physical examination, and abnormal ECG, 626,627 although the specificity is modest. 618,627,630,633 It should be remembered that children may not be able to clearly communicate specific symptoms. Exertional syncope has been associated with LQTS and CPVT.…”
Section: Pediatric Syncope: Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…624,628 Risk factors that raise suspicion of a cardiac etiology include the absence of prodromal symptoms, presence of preceding palpitations within seconds of loss of consciousness, lack of a prolonged upright posture, syncope during exercise or in response to auditory or emotional triggers, family history of SCD, abnormal physical examination, and abnormal ECG, 626,627 although the specificity is modest. 618,627,630,633 It should be remembered that children may not be able to clearly communicate specific symptoms. Exertional syncope has been associated with LQTS and CPVT.…”
Section: Pediatric Syncope: Recommendationsmentioning
confidence: 99%
“…Exertional syncope has been associated with LQTS and CPVT. 315,318,337,630,634 Regardless of symptoms, exertional syncope, especially mid-exertional syncope, should result in a high index of suspicion for a cardiac etiology. See Online Data Supplement 40.…”
Section: Pediatric Syncope: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasovagal syncope is common in adolescents, with a peak incidence in the mid teenage years. Prior studies have shown that among pediatric syncope patients, the groups with cardiac etiologies have a lower mean age than the noncardiac patients . Further, the diagnosis of vasovagal syncope relies on a detailed history of prodromal symptoms with attention paid to any atypical or worrisome features.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiogenic syncope, such as that caused by the prolonged QTc syndromes (the autosomal dominantly inherited Romano–Ward and autosomal recessively inherited Jervell and Lange-Nielsen syndromes) or other arrhythmias, usually occurs in older children although it may also occur in preschool children. Vigorous exercise rather than sudden pain is the characteristic trigger with syncope occurring during or just after exercise; episodes may also follow a sudden loud noise or severe emotional upset 10 11…”
Section: Differential Diagnosismentioning
confidence: 99%